THE EFFECT OF DISCOUNTS, BRAND IMAGE, AND BRAND TRUST ON CONSUMER SATISFACTION AT MATAHARI DEPARTMENT STORE IN PALU CITY - Moh. Rio Ferdinand; Syamsul Bachri; Zakiyah Zahara; Mohammad Zeylo Auriza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of discounts, brand image , and brand trust on consumer satisfaction at Matahari Department Store in Palu City. This study uses a quantitative approach with a survey method by distributing questionnaires to 96 respondents who are consumers of Matahari Department Store in Palu City. The results of the study indicate that Discounts, Brand Image , and Brand Trust partially have a positive and significant influence on consumer satisfaction. In addition, the three variables simultaneously also have a positive and significant influence on consumer satisfaction. This finding emphasizes the importance of an integrated marketing strategy that combines attractive price promotions (discounts), the formation of a strong and positive brand image, and high brand trust to increase overall consumer satisfaction and support business sustainability in the retail industry, especially Matahari Department Store.